Inula erzurumica (Asteraceae), a new species from East Anatolia (Türkiye) - Yapar, Yakup (Phytotaxa, 2025)
Inula erzurumica is a newly described species from Erzurum Province in eastern Türkiye. It resembles I. tuzgoluensis and I. aucheriana, but can be readily distinguished by very long decurrent leaves, densely corymbiform inflorescence, number of ligulate flowers, and phyllaries in 5–6 rows. A detailed description, photographs, information on ecology, distribution, and conservation status of the new taxon are provided herein.